Electronic commerce trends and practices in Barbados - McClean, Stacey (UWI. Centre for International Services Cave HillBB, 2004)
Examines the impact of e-commerce on industry structures, business practices and processes in Barbados. Seeks to determine what can be done to encourage and facilitate further developement.